Infections in patients with acute luekemia treated with different regimens - T. N. Aleksandrova; V. N. Yadrikhinskaya; I. I. Mulina (Сибирский онкологический журнал)
Patients with acute leukemia are characterized by a high risk of infectious complications due to severe neutropenia, which occurs in most cases of modern treatment regimens. Despite the improvement in cytotoxic and concomitant treatment, infectious remain the main cause of induction mortality. Aim of the study: to analyze the frequency and structure of infectious complications in patients with acute leukemia, who received different chemotherapy regimens. Material and Methods. The retrospective analysis included 40 patients with acute myeloid leukemia (AML) and acute lymphoblastic leukemia (ALL). 30 patients with AML underwent 97 chemotherapy courses which included 7 + 3 program (n=53), low-intensity protocols: azacytidine in combination with venetoclax (n=26), Aza-Ida-Ara-C (n=13), low doses of cytarabine (n=3) and high-dose anti-relapse chemotherapy programs (n=2). 10 patients with ALL received 43 chemotherapy courses: ALL-2009 program (n=41), anti-relapse protocols (n=2). The frequency and duration of myelotoxic agranulocytosis, episodes of infections and the variety of microorganisms in different loci were analyzed. Statistical analysis was performed using the Statteсh v. 4.1.2 program. Results. The median duration of myelotoxic agranulocytosis was significantly higher in patients with AML, treated with 7 + 3 protocol, especially during courses of induction of remission. The most common infectious complications were pneumonia, sepsis, febrile neutropenia, and mucositis. Necrotic enteropathy and stomatitis were significantly more common for AML patients compared to ALL patients (22.7 and 7.0 %, (p=0.025); 18.6 and 2.3 %, (p=0.01), respectively). The most common etiologic factors of infections in patients with acute leukemia were gram-negative microorganisms from Enterobacteriaceae family (40.57 %) and non-fermenting bacteria (15.66 %). The detection rate of metallo-beta-lactamase-producing enterobacteria was 12.45 %. The first-line antibacterial therapy (third-generation cephalosporins with beta-lactamase inhibitor) was effective in 21.62 %, and the secondline therapy effectiveness did not exceed 8.2 %. The choice of third and subsequent line antibiotics in most cases was made taking into account the results of microbiological tests, which increased its effectiveness to 41.54 %. The greatest effectiveness was demonstrated by a combination of two carbapenems (17.07 %), and cefoperazone/sulbactam or carbapenem + co-trimoxazole (19.51 %). Conclusion. Thus, patients with acute leukemia have a high prevalence of carbapenem-resistant gram-negative infections.